„ I only became a playwright when I started to direct“ Interview with Alina Nelega, dramatic author, professor and tutor of the Playwriting MA at the University of Arts in Tîrgu-Mureș - WILK, Elise (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
The present interview with Alina Nelega is centred on the contemporary Romanian dramaturgy. Our discussion focuses on the existing initiatives to encourage emerging playwrights, as well as on topics like the evolution of theatre in Romania after the fall of communism, the director-playwright relationship, the transition of the playwright to the status of dramatic author but also on the image of the country in the Romanian dramaturgy.